Weighted product index and its two-independent-sample comparison based on weighted sensitivity and specificity. Issue 22 (17th November 2018) - Li, Dan-Ling; Peng, Jun-Xiang; Duan, Chong-Yang; Deng, Ju-Min
ABSTRACT: Background: On the basis of statistical methods about index S ( S = SEN × SPE ), we develop a new weighted ways (weighted product index Sw ) of combining sensitivity and specificity with user-defined weights.Methods: The new weighted product index Sw is defined as Sw = ( SEN ) (Youden 1950) 2 w × ( SPE ) (Youden 1950) 2(1− w) Results: For the large sample, the test statistics Z of two-independent-sample weighted product indices can either be a monotonous increasing/decreasing function or a no-monotonous function of weight w . Type I error of this statistics can be guaranteed close to the nominal level of 5%, which is more conservative than the weighted Youden index from simulation.